Atomistic versus holistic semiotics - Lotman, Mihhail (Sign Systems Studies, 2002)
The paper is devoted on the foundations of semiotics. It examines the specific features of Peircean and Saussurean traditions and demonstrates that the basis of all the differences is the different conception of the nature of sign: Peirce proceeds from the substitutive concept, Saussure from the bilateral one. The substitutive construction is atomistic by its nature: it is based on a (single) sign which replaces a (single) object, while bilateral is holistic: it is based on the sign system which is divided into (single) signs. The differences of semiosis in atomistic and holistic approach will be pointed out.